PENGEMBANGAN TAMAN WISATA CURUG CIPEUTEUY DI RESORT BANTARAGUNG SEKSI PENGELOLAAN TAMAN NASIONAL (SPTN) WILAYAH II MAJALENGKA TAMAN NASIONAL GUNUNG CIREMAI - Saputra, Yudha Sujadmoko; Susdiyanti, Tun; Supriono, Bambang (Jurnal Nusa Sylva, 2012)
Yosemite waterfall Cipeuteuy Tourism is one of the attractions that are in Resort Bantaragung National Park Management Section ( SPTN ) Majalengka II region that have natural resources in the form of waterfalls, forests, water resources and beautiful scenery. The experiment was conducted at the waterfall Cipeuteuy Resort Bantaragung National Park Management Section (SPTN) Region II Majalengka Ciremai Mountain National Park (TNGC) of West Java Province. The purpose of this research was conducted : 1) Exploring the potential tourist park Cipeuteuy waterfall as a tourist attraction and educational facility. 2) Knowing the improvement and the development and management of tourist park at Waterfall Resort Cipeuteuy Bantaragung Ciremai Mountain National Park. Research using descriptive method with qualitative and quantitative approaches. Visitors sampling technique is done systematically with purposive sampling, sampling for managers waterfall Cipeuteuy done with saturated sampling (census) and sampling to the public is done with random sampling.The method used to analyze the data is descriptive analysis method and SWOT analysis. Alternative strategy of a combination of factors, namely the power and opportunity factors: 1) Maintain good coordination and cooperation between the Village Resort Bantaragung to empower people together, 2) Invite people who have not been active in the management activities to participate in these activities, 3) Improving the quality of tourism facilities and infrastructure that exist, and 4) Enhance the image of a tourist spot clean and comfortable. Combination of factors, namely the weakness and opportunity factors : 1) Looking for sponsor support, a good cooperation with institutions, 2) Cooperating with local governments, 3) To conduct intensive training of human resources, 4) Adding infrastructure is still lacking, 5) develop effective tourism promotion system. Combination of factors, namely the power and threat factors: 1) Develop a marketing strategy effective tourism services, 2) Adding personnel and facility cleanliness around the tourist areas, 3) Growing interest in local culture and develop a love of local knowledge in local masyarat cultural learning, 4) Hold and expand training programs to area managers, and 5) Increase public participation and government. Combination of factors, namely the weakness and threat factors: 1) Increase the role of NGOs in supporting the development of programs and garden tours waterfall Cipeuteuy community development activities.